2010
DOI: 10.1080/07315724.2010.10719853
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Increasing Consumption of Pulses and Wholegrains in Obese People: A Randomized Controlled Trial

Abstract: Incorporation of pulses and wholegrain foods into a weight loss program resulted in a greater reduction in waist circumference compared with the group consuming a control diet, although no difference in weight loss was noted between groups. Retention of several nutrients was better with the pulse and wholegrain diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 27 publications
0
49
0
1
Order By: Relevance
“…Estimates of GI and GL ranged from a mean GI of 40-54 for the lower-GI groups to 53-86 for the higher-GI groups and a mean GL of w50 g/1000 kcal for lower GL groups compared with 75-120 g/1000 kcal for the higher GL groups (Table 1). Two studies reported GI as percentages, but these were not transformed (35,40). The median difference in GI within each study was 10 units, whereas the median difference in GL was 34 units.…”
Section: Trial Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimates of GI and GL ranged from a mean GI of 40-54 for the lower-GI groups to 53-86 for the higher-GI groups and a mean GL of w50 g/1000 kcal for lower GL groups compared with 75-120 g/1000 kcal for the higher GL groups (Table 1). Two studies reported GI as percentages, but these were not transformed (35,40). The median difference in GI within each study was 10 units, whereas the median difference in GL was 34 units.…”
Section: Trial Characteristicsmentioning
confidence: 99%
“…Two studies included only women (30,36), and 1 study included only men (38). The median number of participants in each trial was 47, with 2 larger trials reporting results from .100 subjects (35,40). Scale for measuring GI (glucose or white bread).…”
Section: Trial Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Venn et al [34] conducted an 18-month randomized controlled trial study in 18 overweight volunteers in New Zealand. Diets were based on the guidelines published by the National Heart Foundation of New Zealand, which included a recommendation to eat at least 6 servings of breads and cereals each day.…”
Section: Intervention Studiesmentioning
confidence: 99%
“…Four randomised controlled trials were identified that presented evidence on dietary fibre in relation to blood glucose, all of which were included in a meta-analysis (Aller et al, 2004;Thompson et al, 2005;Andersson et al, 2007;Olendzki et al, 2009). Two trials were identified in the update search (Venn et al, 2010;Weickert et al, 2011) (Aller et al, 2004;Thompson et al, 2005;Andersson et al, 2007). No further trials were identified in the update search (Cardiometabolic review, diabetes and glycaemia chapter p 273-276).…”
mentioning
confidence: 99%